Concurrent management of myopic choroidal neovascularization and rhegmatogenous retinal detachment with intravitreal antivascular endothelial growth factor during primary retinal detachment repair - Saurabh, Kumar (Indian J Ophthalmol, 2018)
We report concurrent management of rhegmatogenous retinal detachment and myopic choroidal neovascularization in the left eye of a 24-year-old female who presented with sudden dimness of vision due to retinal detachment and choroidal neovascularization. Intravitreal antivascular endothelial growth factor was injected during primary vitrectomy for retinal detachment. At final follow-up, the retina was attached with scarring of choroidal neovascularization. Ours is the first report of the use of intravitreal antivascular endothelial growth factor during vitrectomy for retinal detachment.